Estimativa de erosão utilizando a Equação Universal de Perdas de Solos (EUPS): o caso do alto curso do rio Chopim - Basso, Bruna Tauana (2018)
The erosive process ocurrs naturally, however it is being accelerated by anthropic action causing changes in the natural characteristics of soil, reduction of crop productivity, rivers silting and several environmental problems. The implementation of sustainable studies models in watershed, aims preservation, utilization and dinamic of the environment, having an important role as environmental resources management tool. This study aims to establish estimation of soil loss to upper course of Chopim River watershed through aplication of Universal Soil Loss Equation (USLE), applying Qgis 3.0 software. The study area is located in the south of Paraná State. Were considered pluviosity rainfall data from 1985 to 2015 to calculate annual average erosivity and was obtained a variation from 9752 Mj/ha.mm/year to 8180Mj/ha.mm/year, constituting an moderate to strong erosivity. The present soils in the study area have an average erosivity of 0,02030, 0,02092, 0,02410 and 0,02681 Mg.ha.h.ha-1.MJ-1.mm-1 for Nitosol, Latosol, Cambisol, Neosol, respectively. The declivity degree associated with ramp length results in topographic factor, which indicated the study area with flat and smooth wavy relief. The factors of use, management and conservation practices of soil, were estimated according to soil use classification and literature review, alternating from 0 to 0,143. The types of use soil classes were differentiated by Pine, Forest, Open Fields, Conventional Cultivation and Exposed Soil, Urban Area. The annual average soil loss was estimated in 39,36 ton/ha.year what can be considered as moderated soil loss. In the maps analysis were not possible to identificate only one factor that individualizes as soil losses. However, was observed that the association of the erosivity factor and the topographic factor, indicates the high values of soil loss. Nevertheless, the soil loss estimation map in the upper course of the watershed of Chopim River provides enough data to the analysis and environmental planning of study area.